1993
DOI: 10.1111/j.1469-7610.1993.tb01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Psychosocial Experiences in Childhood: Methodological Issues and Some Illustrative Findings

Abstract: The development of a new standardised investigator-based interview, PACE (Psychosocial Assessment of Childhood Experiences), for the assessment of acute life events and long-term psychosocial experiences is described. An application of PACE to a sample of 84 children referred to psychiatric clinics and 22 general population controls, is presented. Reliability was assessed using a separate clinic sample of 15 child-parent pairs. The findings showed that PACE has satisfactory reliability and discriminant validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…These reviews point to evidence that younger and older people's reports of their childhoods are more in accord with those of independent observers than with their parents' reports. The agreement between parents and their children on reports of stressful life events is also weak (Sandberg et al, 1993). One reason for this is that childhood experiences outside of the home may not be known about or shared with parents.…”
Section: Resultsmentioning
confidence: 99%
“…These reviews point to evidence that younger and older people's reports of their childhoods are more in accord with those of independent observers than with their parents' reports. The agreement between parents and their children on reports of stressful life events is also weak (Sandberg et al, 1993). One reason for this is that childhood experiences outside of the home may not be known about or shared with parents.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast chronic adversities may reflect stable characteristics of the child, their family or the broader social context (e.g., health problems, discrimination). Indeed, Sandberg et al (1993) found that approximately 80% of chronic adversities lasted at least a year in a sample of children referred to psychiatric clinics. Alternatively, the occurrence of chronic adversities may produce long-term changes that increase the child's vulnerability regardless of whether or not the stressor remains present (e.g., parental unemployment results in financial difficulties that persist even after the parent finds a new job).…”
Section: Discussionmentioning
confidence: 99%
“…The Psychosocial Assessment of Childhood Experiences: Parent Version (PACE; Glen et al 1993;Sandberg et al 1993) is a standardized investigator-based interview designed to assess life events and chronic adversities experienced by children. This interview was based on the principles of the Life Events and Difficulties Schedule (LEDS; Brown and Harris 1978).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these (up to 80%) last at least a year. 15 The present analyses were based on children with low to moderate chronic stress (up to three highly negative long term experiences).…”
Section: Measurement Of Chronic Stress (Long Term Experiences)mentioning
confidence: 99%